Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Antiplasmid activity of 1 `-acetoxychavicol acetate from alpinia galanga against multi-drug resistant bacteria - Latha, C.; Shriram, Varsha D.; Jahagirdar, Sheetal S.; Dhakephalkar, Prashant K.; Rojatkar, Supada R. (Journal of Ethnopharmacology, 2009)
Ethnopharmacological relevance: Alpinia galanga (L.) Swartz is traditionally used in the treatment of various ailments across India, China, and Southeast Asian countries. In India it is a reputed drug in indigenous system of medicine and largely used as antibacterial and antiseptic. In southern India the rhizomes has been used as a domestic remedy against bacterial infections. Aim of the study: To identify a potential antiplasmid compound from Alpinia galanga against multi-drug resistant bacteria. Materials and methods: The crude rhizome extract of Alpinia galanga was prepared in acetone. Antibacterial activity was checked by MIC and antiplasmid activity was checked by SIC. The principal compound responsible for the antiplasmid activity, in the crude extract, was identified by bioassay guided fractionation using hexane-acetone. Antibiotic resistance profile of plasmid harboring strains and plasmid cured strains was determined by disc diffusion method. Results: The crude acetone extract of the rhizomes of Alpinia galanga exhibited antiplasmid activity against Salmonella typhi, Escherichia coli and vancomycin resistant Enterococcus faecalis with an efficiency of 92%, 82% and 8% respectively at 400 mu g/ml SIC. The principal compound responsible for the activity was identified as 1'-acetoxychavicol acetate. 1'-Acetoxychavicol acetate demonstrated the ability to cure plasmid encoded antibiotic resistance in various multi-drug resistant bacterial strains of clinical isolates such as Enterococcus faecalis, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli and Bacillus cereus with curing efficiency of 66%, 75%, 70%, 32% and 6% respectively at SIC of 400-800 mu g/ml. Conclusion: 1'-Acetoxychavicol acetate mediated R-plasmid curing significantly reduced the minimal inhibitory concentration of antibiotics required to inhibit growth of bacteria, thus making the antibiotic treatment more effective. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: 1 `-Acetoxychavicol acetate; Alpinia galanga; Antibiotic resistance; Antiplasmid

Antibacterial & antiplasmid activities of Helicteres isora L. - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Dhakephalkar, Prashant K.; Rojatkar, Supada; Shitole, Mahadeo G. (Indian Journal of Medical Research, 2010)
Background & objectives: The multiple drug resistance (MDR) is a serious health problem and major challenge to the global drug discovery programmes. Most of the genetic determinants that confer resistance to antibiotics are located on R-plasmids in bacteria. The present investigation was undertaken to investigate the ability of organic extract of the fruits of Helicteres isora to cure R-plasmids from certain clinical isolates. Methods: Active fractions demonstrating antibacterial and antiplasmid activities were isolated from the acetone extracts of shade dried fruits of H. isora by bioassay guided fractionation. Minimal inhibitory concentration (MIC) of antibiotics and organic extracts was determined by agar dilution method. Plasmid curing activity of organic fractions was determined by evaluating the ability of bacterial colonies (pre treated with organic fraction for 18 h) to grow in the presence of antibiotics. The physical loss of plasmid DNA in the cured derivatives was further confirmed by agarose gel electrophoresis. Results: The active fraction did not inhibit the growth of either the clinical isolates or the strains harbouring reference plasmids even at a concentration of 400 mu g/ml. However, the same fraction could cure plasmids from Enterococcus faecalis, Escherichia coli, Bacillus cereus and E. coli (RP4) at curing efficiencies of 14, 26, 22 and 2 per cent respectively. The active fraction mediated plasmid curing resulted in the subsequent loss of antibiotic resistance encoded in the plasmids as revealed by antibiotic resistance profile of cured strains. The physical loss of plasmid was also confirmed by agarose gel electrophoresis. Interpretation & conclusions: The active fraction of acetone extract of H. isora fruits cured R-plasmids from Gram-positive and Gram-negative clinical isolates as well as reference strains. Such plasmid loss reversed the multiple antibiotic resistance in cured derivatives making them sensitive to low concentrations of antibiotics. Acetone fractions of H. isora may be a source to develop antiplasmid agents of natural origin to contain the development and spread of plasmid borne multiple antibiotic resistance.
Keywords: antibacterial activity; Antibiotic resistance; antiplasmid activity; Helicteres isora; multiple drug resistance; plasmid-curing

Chemical and biological metal nanoparticles as antimycobacterial agents: a comparative study - Singh, Richa; Nawale, Laxman U.; Arkile, Manisha A.; Shedbalkar, Utkarsha U.; Wadhwani, Sweety A.; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Antimicrobial Agents, 2015)
Resistance among mycobacteria leading to multidrug-resistant and extensively drug-resistant tuberculosis is a major threat. However, nanotechnology has provided new insights in drug delivery and medicine development. This is the first comparative report to determine the activity of chemically and biologically synthesised silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) against mycobacteria. Screening data revealed the high mycobactericidal efficiency of AgNPs, with minimum inhibitory concentrations (MICs) of <3 mu g/mL, whereas no such activity was exhibited by AuNPs at concentrations up to 100 mu g/mL. Moreover, in vitro and ex vivo THP-1 infection model assays showed greater efficacy of chemical AgNPs compared with biogenic AgNPs to inhibit active and dormant stage mycobacterial growth. Up to 40% cytotoxicity against human cell lines was observed at a AgNP concentration of 10 x MIC (30 mu g/mL) after 48 h. AgNPs were shown to have more specificity towards mycobacteria than towards other Gram-negative and Gram-positive pathogenic bacteria. The selectivity index was found to be in the range of 11-23, indicating the potential of these nanoparticles for use in developing new therapeutics for tuberculosis. (C) 2015 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: Antibiotic resistance; Antimycobacterial agent; Cytotoxicity; Mycobacteria; Nanoparticles; tuberculosis

Detection of ciprofloxacin residues in cow milk: a novel and rapid optical beta-galactosidase-based screening assay - Kalunke, Raviraj M.; Grasso, Gerardo; D'Ovidio, Renato; Dragone, Roberto; Frazzoli, Chiara (Microchemical Journal, 2018)
Ciprofloxacin (a member of the fluoroquinolone class) is one of the most widely used antibacterial agents for the treatment of bacterial infections in livestock. The improper use of such antibacterial agents could lead to the presence of residues in animal origin foods (including milk) and consequently harmful effects for health of consumers, together with the spread of antibiotic-resistant bacterial strains. Therefore, in order to support good farming practices and to ensure food safety, antimicrobial (in particular fluoroquinolones) residues surveillance through improved monitoring techniques is crucial. However, commercial available kits for the detection of fluoroquinolones residues in food samples are time-consuming and still fail to detect MRL concentrations for fluoroquinolones (e.g. 0.1 mg/kg for the sum of enrofloxacin and ciprofloxacin residues). Here a novel and rapid assay for ciprofloxacin residual detection through optical microbiological screening in commercially pasteurized cow's milk samples is described. Escherichia coli ATCC 11303 cell proliferation was optically monitored by measuring endogenous (beta-gal activity that was determindd through colorimetric assay in the presence of a chromogenic beta-gal artificial substrate. Optical density of E. coli cell culture (linked to cell proliferation) was positively correlated with endogenous beta-gal activity. As the presence of ciprofloxacin residues inhibits the E. coli cell proliferation in tested samples, (3-gal levels decreased more in exposed samples than in control. The essential step of beta-gal induction (usually obtained by IPTG) was obtained by exploiting the lactose present in the milk. Our findings show a detection of ciprofloxacin residues at 1 MRL concentration after 1 h using ONPG as chromogenic 3 gal artificial substrate and lactose as (3-gal inducer. Compared to previously described methods, this assay proved to be a rapid, proficient and more eco-friendly (i.e. minimizing the use of additional reagents) system that could be potentially employed as screening method for detection ciprofloxacin residues in cow's milk. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Antibiotic resistance; Farm animals; Fluoroquinolones; HACCP; One health; Primary production; Risk assessment and management

Comprehensive metagenomic insights into a unique mass gathering and bathing event reveals transient influence on a riverine ecosystem - Yadav, Rakeshkumar; Rajput, Vinay; Gohil, Kushal; Khairnar, Krishna; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
The religious mass gathering and bathing can pose a multitude of significant public health challenges and lead to severe alterations in the river microbial ecology. The Pandharpur Wari is an annual pilgrimage of Maharashtra, India, where millions of devotees carry the footprints of the saint-poets and pay their obeisance to Lord Vitthal on the 11th day of moon's waxing phase (Ashadi Ekadashi). As a part of the ritual, the engrossed devotees, walk over 250 km, take a first holy dip in a sacred river Indrayani at Alandi and secondly in Bhima River at Pandharpur. The MinION-based shotgun metagenomic approach was employed to examine the impact of spiritual mass bathing on environmental changes (concerning the river microbial community structure and functions); and public health aspects (in terms of changes in the pathogenic potential and antibiotic resistance). The analysis of bathing and post-bathing samples of both the rivers revealed alterations in the alpha and beta diversity, indicating significant spatiotemporal variations in the overall microbial structure and function. Furthermore, the analysis revealed up to 80% of differences in the abundance of virulence genes between the bathing and post bathing samples. We observed parallel increase of priority skin and enteric pathogens (ranging from 11% to 80%) such as Acinetobacter baumannii, Staphylococcus aureus, Streptococcus pyogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa during the bathing event. Moreover, we observed a significant increase in the antibiotic resistance in the bathing samples of Bhima and Indrayani rivers respectively. Altogether, this is the first comprehensive metagenomic study unravelling the influence of religious mass-bathing on the riverine ecosystem.
Keywords: Antibiotic resistance; Mass bathing; MinION sequencing; Priority pathogens; Virulence genes

Pan-genomics of Ochrobactrum species from clinical and environmental origins reveals distinct populations and possible links - Gohil, Kushal; Rajput, Vinay; Dharne, Mahesh (Genomics, 2020)
Ochrobactrum genus is comprised of soil-dwelling Gram-negative bacteria mainly reported for bioremediation of toxic compounds. Since last few years, mainly two species of this genus, O. intermedium and O. anthropi were documented for causing infections mostly in the immunocompromised patients. Despite such ubiquitous presence, study of adaptation in various niches is still lacking. Thus, to gain insights into the niche adaptation strategies, pan-genome analysis was carried out by comparing 67 genome sequences belonging to Ochrobactrum species. Pan-genome analysis revealed it is an open pan-genome indicative of the continuously evolving nature of the genus. The presence/absence of gene clusters also illustrated the unique presence of antibiotic efflux transporter genes and type IV secretion system genes in the clinical strains while the genes of solvent resistance and exporter pumps in the environmental strains. A phylogenomic investigation based on 75 core genes depicted better and robust phylogenetic resolution and topology than the 16S rRNA gene. To support the pan-genome analysis, individual genomes were also investigated for the mobile genetic elements (MGE), antibiotic resistance genes (ARG), metal resistance genes (MRG) and virulence factors (VF). The analysis revealed the presence of MGE, ARG, and MRG in all the strains which play an important role in the species evolution which is in agreement with the pan-genome analysis. The average nucleotide identity (ANI) based on the genetic relatedness between the Ochrobactrum species indicated a distinction between individual species. Interestingly, the ANI tool was able to classify the Ochrobactrum genomes to the species level which were assigned till the genus level on the NCBI database.
Keywords: Antibiotic resistance; Average nucleotide identity; Clinical and environmental strains; Core genes; MinION; Virulence factors

Metagenomic exploration reveals a differential patterning of antibiotic resistance genes in urban and peri-urban stretches of a riverine system - Rajput, Vinay; Yadav, Rakeshkumar; Dharne, Mahesh S. (Environmental Science and Pollution Research, 2021)
{Antimicrobial resistance in the riverine ecosystem of urban areas is an alarming concern worldwide, indicating the importance of molecular monitoring to understand their patterning in urban and peri-urban areas. In the present study, we evaluated the influence of urban rivers on the connected peri-urban rivers of a riverine system of India in the context of antibiotic resistance genes. The rivers traversing through urban (Mula, Mutha, Pawana, and Ramnadi) and peri-urban stretches (Bhima and Indrayani) form the riverine system of Pune district in Maharashtra, India. The MinION-based shotgun metagenomic analysis revealed the resistome against 26 classes of antibiotics, including the last line of antibiotics. In total, we observed 278 ARG subtypes conferring resistance against multiple drugs (40%), bacitracin (10%), aminoglycoside (7.5%), tetracycline (7%), and glycopeptide (5%). Further, the alpha diversity analysis suggested relatively higher ARG diversity in the urban stretches than peri-urban stretches of the riverine system. The NMDS (non-metric multidimensional scaling) analysis revealed significant differences with overlapping similarities (stress value = 0.14
Keywords: Antibiotic resistance; MinION; Peri-urban rivers; Urbanization

PNA-mediated efflux inhibition as a therapeutic strategy towards overcoming drug resistance in Mycobacterium smegmatis - Ghosh, Saptarshi; Cotta, Karishma Berta; Hande, Aniket A.; Fernandes, Moneesha; Mehra, Sarika (Microbial Pathogenesis, 2021)
The emergence of antibiotic-resistant strains of Mycobacterium tuberculosis and the decelerating development of new and effective antibiotics has impaired the treatment of tuberculosis (TB). Efflux pump inhibitors (EPIs) have the potential to improve the efficacy of existing anti-TB drugs although with toxicity limitations. Peptide nucleic acids (PNAs), oligonucleotide mimics, by virtue of their high nucleic acid binding specificity have the capability to overcome this drawback. We, therefore, investigated the efflux pump inhibitory properties of a PNA designed against an efflux pump of Mycobacterium smegmatis. LfrA, an efflux pump found in M. smegmatis, is majorly involved in conferring innate drug resistance to this strain and, therefore, was selected as a target for gene silencing via PNA. qRT-PCR and EtBr assays confirmed the EPI activity of the anti-lfrA PNA. On testing the effect of the anti-lfrA PNA on the bactericidal activity of a fluoroquinolone, norfloxacin, we observed that 5 mu M of anti-lfrA PNA in combination with norfloxacin led to an enhanced killing of up to 2.5 log-fold against wild-type and a lab-generated multidrug resistant strain, exemplifying its potential in countering resistance. Improved efficacy was also observed against intra-macrophage mycobacteria, where the drug-PNA combination enhanced bacterial clearance by 1.3 log-fold. Further, no toxicity was observed with PNA concentrations up to 4 times higher than the efficacious anti-lfrA PNA concentration. Thus, PNA, as an adjuvant, presents a novel and viable approach to rejuvenate anti-TB therapeutics.
Keywords: Adjuvant; Antibiotic resistance; Antisense; Efflux pump; Gene silencing; Mycobacteria; Peptide nucleic acid (PNA)

Systemic review on fitness and survival of salmonella in dynamic environment and conceivable ways of its mitigation - Sutar, Ajit A.; Dashpute, Rohit S.; Shinde, Yashodhara D.; Mukherjee, Srestha; Chowdhury, Chiranjit (Indian Journal of Microbiology, 2024)
Gastroenteritis caused by non-typhoidal Salmonella still prevails resulting in several recent outbreaks affecting many people worldwide. The presence of invasive non-typhoidal Salmonella is exemplified by several characteristic symptoms and their severity relies on prominent risk factors. The persistence of this pathogen can be attributed to its broad host range, complex pathogenicity and virulence and adeptness in survival under challenging conditions inside the host. Moreover, a peculiar aid of the ever-changing climatic conditions grants this organism with remarkable potential to survive within the environment. Abusive use of antibiotics for the treatment of gastroenteritis has led to the emergence of multiple drug resistance, making the infections difficult to treat. This review emphasizes the importance of early detection of Salmonella, along with strategies for accomplishing it, as well as exploring alternative treatment approaches. The exceptional characteristics exhibited by Salmonella, like strategies of infection, persistence, and survival parallelly with multiple drug resistance, make this pathogen a prominent concern to human health.
Keywords: Antibiotic resistance; Gastroenteritis; Non-typhoidal Salmonella; pathogenesis; Plant-derived metabolites; Salmonella pathogenicity islands; Type III secretion system